Study of legal documents in the field of official business style - Zhanzhigitov С.Ж.; Abdualiuly Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The time when legal texts began to be discussed separately in the Kazakh linguistics and be studied independently coincides with the time of formation and gaining independence by the Kazakh state. Therefore, the study of the language of legal documents, identification of their features is of great importance, first of all, for lawmaking. The legislative body should keep the linguistic structure of legislative documents in the center of attention and strictly ensure that they contain no unnecessary words. The purpose of the article is to study the peculiarities of translating legal texts from Russian into Kazakh, to identify the shortcomings in the translation of legal acts into the state language along with theoretical translation issues. During the writing of the article, all the requirements of the official business style were fully found in the text of the law, as well as informative, pragmatic and cognitive activity in the structure of law was analyzed. This is the major scientific novelty of the article. This article has theoretical and practical significance, since the presented concept is valuable information for students of the legal field. It is necessary to emphasize once again that in order to fully master the profession, it is necessary to know and correctly use lexical units called special concepts, i.e., terms. A systematic approach to the study of industry terminology, considered on the example of legal terminology, leads to the optimization of the learning process. Lexical and conceptual correspondence of terms, their interrelation and dependence on each other allow us to consider terminology as an integral terminological system that serves as a kind of linguistic basis for a system of special concepts. This, in turn, reflects the consistency of scientific knowledge. The main characteristics of legal terminology were considered, the system structure was studied and proved. A systematic approach to the study of industry terminology will undoubtedly optimize the learning process.